3D FE Analysis of an Embankment Construction on GRSC and Proposal of a Design Method. (7th March 2013) - Tandel, Yogendra K.; Solanki, Chandresh H.; Desai, Atul K.
Abstract : Stone column is often employed for strengthening of an embankment seated on deep soft clay. But in very soft clay having undrained shear strength less than or equal to 15 kPa, stone column may not derive adequate load carrying capacity and undergo large lateral deformation due to inadequate lateral confinement. In such circumstances, reinforcement to individual stone column by geosynthetics enhances load carrying capacity and reduces lateral deformation. This paper addresses parametric study on behaviour of embankment resting on Geosynthetic Reinforced Stone Column (GRSC) considering parameters such as stone column spacing to diameter ratio, deformation modulus of stone column material, geosynthetic stiffness, thickness of soft clay, and height of embankment by 3D numerical analysis. Finally, equation for Settlement Improvement Factor (SIF), defined as ratio between settlement of embankment without treatment and with geosynthetic reinforced stone column, is proposed that correlates with the major influence parameters such as stone column spacing to diameter ratio, deformation modulus of soft clay, and geosynthetic stiffness.